Tingkat Keberlanjutan Sosial-Ekonomi Desa Pela Kalimantan Timur Berdasarkan Sustainable Development Goals (SDGs) - Ema Dwi Arsita; Demayanti Asikin; Ema Yunita Titisari (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
Pela Village is in Kutai Kartanegara Regency, East Kalimantan Province, this village is unique in that part of its area is a water area. Pela Village is designated as a lake and river-based tourist village with the Mahakam Pesut ecosystem, this is due to the geographical position of Pela village which is at the mouth of the Mahakam river and Lake Semayang. The challenge of developing tourist attractions in the region is the large tourism potential it has, but the limited capacity of community resources to develop it. The aim of the research is to determine the level of sustainability of Pela Village from social and economic aspects in relation to the Sustainable Development Goals (SDGs), using the exploratory descriptive qualitative method. The results of the research explain that the people of Pela Village have a good level of sustainability because they practice environmentally friendly living and are supported by the conservation of the Mahakam Pesut. There needs to be good planning so that the Pela tourist village can continue to develop so as to produce ecotourism and a sustainable built environment.